THE EFFECT OF HUMAN RESOURCE COMPETENCE AND ORGANIZATIONAL CULTURE ON THE QUALITY OF SERVICES IN BATUDAA PUSKESMAS GORONTALO DISTRICT (Journal of Economic, Business, and Administration (JEBA), 2024)
The purposes of this study are: 1) To determine and analyze the partial effect of HR competence on service quality at Batudaa Health Center, Gorontalo Regency; 2) To find out and partially analyze the influence of organizational culture on service quality at Batudaa Health Center, Gorontalo Regency; 3) To determine and analyze the simultaneous influence of HR competence and organizational culture on service quality at Batudaa Health Center, Gorontalo Regency.  This research is a quantitative descriptive approach Research results: 1) Human resource competence has a partial effect on service quality with a contribution of 63.4% influence. Thus, the hypothesis in this study assumes that the competence of human resources has a partial effect on service quality and has been proven and can be accepted; 2) Organizational Culture has a partial effect on Service Quality with an influence contribution of 26.6%. Thus, the hypothesis in this study suggests that organizational culture has a partial effect on service quality and has been proven and can be accepted; 3) Human Resource Competence and Organizational Culture simultaneously have a simultaneous effect on Service Quality with an influence contribution of 72.20%. Thus the hypothesis in this study assumes that the competence of HR and Organizational Culture simultaneously has a simultaneous effect on Service Quality has been proven and can be accepted.
Keywords: HR Competence, Organizational Culture, Affecting Service Quality